Associations of metals with hemoglobin and anemia in a Chinese early adolescent cohort - Mengyuan Yuan; Ting Tang; Yonghan Li; Xinhui Wang; Cong Wang; Xueying Zhang; Yichao Huang; Fangbiao Tao; Gengfu Wang; Daomin Zhu; Feng Geng; Puyu Su (Ecotoxicology and Environmental Safety)
Background: The relationship between exposure to metals with hemoglobin levels and anemia in children and adolescents has shown inconsistency. This study aimed to evaluate the associations of individual metals and metal mixtures with hemoglobin levels and anemia risk, as well as potential sex differences, in a Chinese early adolescent cohort. Methods: Data was obtained from a Chinese early adolescent cohort with two-year follow-up periods. Serum concentrations of 12 metals were measured using inductively coupled plasma mass spectrometry (ICP-MS). To examine the individual associations of metals with hemoglobin levels and anemia risk, a series of single-metal and multi-metal adjusted generalized linear mixed models (GLMMs) were applied. Additionally, quantile g-computation (qgcomp) and Bayesian kernel machine regression (BKMR) were used to analyze the effects of metal mixture. Furthermore, all analyses were stratified by sex. Results: The multi-metal adjusted GLMMs identified significant associations of As (β=2.31; 95 % CI: 0.15, 4.47), Cd (β=-2.11; 95 % CI: −4.11, −0.11), Cr (β=-10.19; 95 % CI: −19.09, −1.30), Cu (β=-7.27; 95 % CI: −14.27, 0.26), Fe (β=13.71; 95 % CI: 10.03, 17.38), Pb (β=7.87; 95 % CI: 4.21, 11.5), V(β=-13.60; 95 % CI: −21.32, −5.88), and Zn (β=14.77; 95 % CI: 4.38, 25.15) with hemoglobin concentration, as well as As (OR=0.26; 95 % CI: 0.11, 0.60), Co(OR=4.27; 95 % CI: 1.25, 14.6), Cr (OR=10.49; 95 % CI: 1.61, 68.39), Fe (OR=0.03; 95 % CI: 0.01, 0.12) and Pb (OR=0.18; 95 % CI: 0.04, 0.80) with anemia risk. Moreover, the qgcomp revealed no association of metal mixture with hemoglobin concentration (β=0.94; 95 % CI=-0.45, 2.33) or anemia risk (OR=0.81; 95 % CI: 0.51, 1.27). After stratification by sex, the qgcomp demonstrated no significant overall effect of the metal mixture on hemoglobin concentration or anemia risk in either boys (β=0.93; 95 % CI: −0.84, 2.71 for hemoglobin, and OR=0.64; 95 % CI: 0.27, 1.52 for anemia) or girls (β=0.93, 95 % CI: −1.16, 3.01 for hemoglobin, and OR=0.72; 95 % CI: 0.40, 1.32 for anemia). Similarly, sex-stratified BKMR models also revealed no significant association between the metal mixture and hemoglobin concentration or anemia risk in either boys or girls. Conclusions: This study highlights the individual and collective impacts of 12 metals on hemoglobin and anemia during early adolescence, underscoring the need for experimental and larger cohort studies to further corroborate these findings.